719 The Routine Use of Opioid Medication for Post-Operative Pain Relief Can Risk Long Term Dependence, In Patients Previously Opiate Naive. (4th May 2021) - McGurk, S; Majeed, T; Magee, C
Abstract: Introduction: Post-operative pain relief commonly involves opiates. Rising concerns about misuse has increased scrutiny of prescribing practices. In the UK, 12.5% of prescriptions are for opiates. In the US, the Department of Health and Human Services has declared an epidemic of opiate misuse. We aimed to evaluate opiate prescribing practices post-operatively, within a UK teaching hospital, and establish the risk of prolonged opiate use. Method: A pan-speciality retrospective observational cohort study was performed. Patients who underwent surgery in the year 2018 were included. Patients were opiate naïve if their admission Medicine reconciliation and GP record described no opiates for the previous year. Endpoints: the proportion of patients discharged with opiates and the proportion of patients remaining on opiates at 1- and 2-years post admission. Results: 20526 operations were performed on 17524 patients, across pan-specialities. 8772 patients were discharged on opiates. 673 required further opiates from their GP after discharge, of which 331 were previously opiate naive. At 1 year post op, 180 previously naive patients remained on opiates. Conclusions: Attention needs to be given to the risk of developing opiate dependence post-operatively. An evidence-based approach should support clinicians in preventing an opiate crisis in the UK.